Analisis Perancangan Sistem Tata Udara dan Pendingin Ruangan pada Data Center untuk Mengurangi Resiko Down Time Menggunakan PPDIOO Network Life-Cycle: (Studi Kasus di Universitas Krisnadwipayana) - Abdul Sodiq Amrulloh; Ayub Muktiono; Jenni Ria Rajagukguk (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The reliability of a data center is highly dependent on its air conditioning and cooling system. This research evaluates the existing cooling system of Universitas Krisnadwipayana’s data center using the PPDIOO Network Life-Cycle approach. The study finds that the current cooling system, which relies on AC Split, fails to meet TIA-942 standards, posing significant overheating risks and increasing downtime probability. Observational analysis shows that the cooling distribution is inefficient due to inadequate airflow and the absence of a structured cooling layout. To address these issues, this research proposes an optimized cooling system design that incorporates Computer Room Air Conditioning (CRAC), hot aisle-cold aisle arrangement, and raised floor implementation. The recommended improvements also include installing temperature and humidity sensors for real-time environmental monitoring and implementing N+1 redundancy for enhanced system reliability. These solutions are expected to improve cooling efficiency, reduce energy consumption, and mitigate downtime risks. Future research should focus on evaluating the practical impact of this design by conducting real-world trials and exploring liquid cooling technology as a potential alternative for further efficiency improvements.